3D food printing– sustainability through food waste upcycling. (2022) - Hooi Chuan Wong, Gladys; Pant, Aakanksha; Zhang, Yi; Kai Chua, Chee; Hashimoto, Michinao; Huei Leo, Chen; Tan, U-Xuan
Abstract: 'Circular economy' and 'zero waste economy' are not just 21st century terms but are increasingly becoming part of mainstream narrative to lead an ethical and environmentally conscious life which benefits not just humans but the entire ecosystem. Innovative approaches are being targeted to achieve this mission, one being revalorization of food waste to value added products. Food wastage occurs from the initial steps of agricultural produce to industrial manufacturing and processing, to retail and household consumption. The greatest culprit in generating waste is the common households. 3D food printing (3DFP) is one of the emerging technologies that can be effectively utilized to target food wastes from different sources. Consumer acceptance of food waste as edible food still has many barriers. 3DFP can help rescue certain waste types to generate customized and personalized beautiful designs familiar in taste and form for easier acceptability. We have demonstrated the 3D printability of jackfruit seeds that are often underutilized and discarded as waste. Subjecting the waste to simple and effective cooking techniques helped to prepare food ink suitable for 3D printing. Further studies are planned to improve and characterize the inks further to achieve better prints.